Soul, Triangle and Virtue. On the Figure of Implicit Comparison in Plato’s Meno - Palumbo, Lidia (Peitho. Examina Antiqua, 2017)
Plato’s dialogues can be regarded as the most important documents of the extraordinary mimetic power of visual writing, i.e., writing capable of “showing” and “drawing images” by using words only. Thanks to the great lesson of the Attic theater, Plato makes his readers see: when reading the dialogues, they see not only the characters talking but owing to the visual power of mimetic writing, they also see that which the characters are actually talking about. There are numerous rhetorical devices employed by Plato the writer that make this visual rendering of philosophy possible. In this text, I would like to bring an example from the Meno that illustrates the visual power of an implicit comparison. By “implicit comparison”, I mean the special kind of comparison that is not presented explicitly and fully in the text but that the text merely evokes and that, once evoked, contributes to determining the formation of the image.